The Visegrád Group's policy towards Israel: Common values and interests as a catalyst for cooperation - Joanna Dyduch (Stiftung Wissenschaft und Politik (SWP), 2018)
Since 2017, relations between the Visegrád Group (V4) and Israel have been changing. Hungary, Poland, the Czech Republic, and Slovakia are increasingly developing shared views and values on international politics and show a greater willingness to cooperate economically. This coincides with growing European Union (EU) criticism of the Israeli government's stance on the Arab-Israeli conflict. However, the V4 states' leaders do not necessarily share that criticism, and they have even aligned themselves with Israeli viewpoints on issues such as migration, security, and threat perceptions, all of which are disputed in the EU. The EU needs to be aware that this positioning of the V4 states might lead to a growing internal divergence concerning its Israel policy. This would especially hold true if it were to increase pressure on Israel, as some EU members envisage.
Keywords: 320